2020
DOI: 10.1002/uog.20379
|View full text |Cite
|
Sign up to set email alerts
|

Learning curve for detection of pelvic parts of ureters by transvaginal sonography: feasibility study

Abstract: CONTRIBUTIONWhat are the novel findings of this work? Sonographers and/or gynecologists who are familiar with gynecological transvaginal sonography (TVS) should be able to become proficient in identifying the pelvic parts of both ureters after 40-50 TVS examinations. What are the clinical implications of this work?Detection of ureters is a feasible part of the TVS workup of women attending a tertiary referral center clinic. In deep infiltrating endometriosis, identification of ureters and diagnosis of proximal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 23 publications
0
13
0
1
Order By: Relevance
“…It may not be appropriate to suggest that learning how to visualize the ureters is possible in a set number of examinations, as all individuals learn differently with various strengths and weaknesses. This idea is in contrast to a recently published feasibility study, 28 which concluded that around 40 to 50 TVUS examinations are necessary to be capable of identifying the ureters with TVUS. We advocate for a competency‐based educational model rather than a “one‐size‐fits‐all” approach.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…It may not be appropriate to suggest that learning how to visualize the ureters is possible in a set number of examinations, as all individuals learn differently with various strengths and weaknesses. This idea is in contrast to a recently published feasibility study, 28 which concluded that around 40 to 50 TVUS examinations are necessary to be capable of identifying the ureters with TVUS. We advocate for a competency‐based educational model rather than a “one‐size‐fits‐all” approach.…”
Section: Discussionmentioning
confidence: 69%
“…Our time limit to identify the ureters was 120 seconds compared to 150 seconds. This should have little bearing, as each of the participants in the study by Aas-Eng et al 28 identified bilateral ureters in less than 30 seconds in each case, with a median time to identify ureters ranging from 4 to 20 seconds. This was also consistent with a study by Pateman et al 13 that reported bilateral ureter identification in a median of 8 to 9 seconds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Improvements in gynecological ultrasound training in residency programs is recommended. In curriculum planning, there are now a number of learning-curve studies for detecting DE using TVS to use as guidance [18][19][20] .…”
Section: Why Does It Take So Long To Introduce Novel Concepts and Tecmentioning
confidence: 99%